Spatial-temporal evolution and proximity mechanism of urban networks in China from the multiplicity perspective - Tang, Chenghui; Chai, Jianan (Frontiers in Physics, 2022)
As the important performance of inter-city interaction, urban network have the significant impact on urban system and economic development of city-regions. However, previous studies mainly analyzed the structure of single urban network from the static perspective and lacked in-depth analysis of the driving mechanism of network evolution. Based on the headquarters-branch data of companies and patent transaction data, this paper uses spatial analysis, social network analysis and negative binomial regression analysis to explore the structure evolution and proximity mechanism of urban networks in China. The empirical results were as follows: Firstly, different types of urban networks are characterized by stratification and geographical unevenness, and the evolution of urban networks show priority linkage and path dependence. Secondly, the Yangtze River Delta, the Pearl River Delta and the Beijing-Tianjin-Hebei urban agglomerations shape high-value agglomeration centers, but show a differentiated development trend. Thirdly, geographical proximity has the stronger effect on urban innovation network evolution, but institutional and cultural proximity has the stronger effect on urban economic network evolution. The comparative study of urban networks not only helps to clarify the structure and characteristics of urban system, but also contributes to a comprehensive understanding of the diversity and complexity of inter-city interactions.